Hubungan antara Stres Akademik dan Prokrastinasi Akademik dengan Prestasi Belajar Siswa Kelas X Sekolah Menengah Atas - Lia Artika Sari; Djoko Budi Santoso; Ella Faridati Zen (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: The purpose of this study is to determine the relationship between academic stress and academic procrastination with learning achievement. This study used a correlational research design. The population of this research was the X graders of SMA Brawijaya Smart School Malang with a total of 194 students, the research sample totaling 100 students obtained using the Slovin formula with an error tolerance of 7 percent. The sampling using simple random sampling method. This study used research instrument in the form of scales. First, "Student Life Stress Inventory" scale which was adapted in Indonesian by (Rohana, 2017). Second, the academic procrastination scale developed by the author based on the characteristics of academic procrastination according to (Ferrari et al., 1995). Both instruments had been tested for validity and reliability. The measurement of learning achievement used the score of the mid-semester exam in the odd semester of 2021/2022. The results showed that academic stress and academic procrastination had a negative relationship with learning achievement and together academic stress and academic procrastination affected learning achievement. Researchers hope the results of this study can be information and considerations for school counselors or BK teachers in providing services to students. In addition, researchers hope that further researchers can continue development research that produces a product that can help students related to problems of academic stress, academic procrastination and learning achievement. Abstrak: Tujuan pada penelitian ini adalah untuk mengetahui hubungan antara stres akademik dan prokrastinasi akademik dengan prestasi belajar. Penelitian ini menggunakan rancangan penelitian korelasional. Populasi penelitian adalah siswa kelas X SMA Brawijaya Smart School Malang sejumlah 194 siswa, sampel penelitian berjumlah 100 siswa yang diperoleh menggunakan rumus slovin dengan tingkat kelonggaran 7% dan pengambilan sampel menggunakan metode simple random sampling. Penelitian ini menggunakan alat ukur atau intrumen penelitian berupa “Student Life Stress Inventory” yang diadaptasi dalam bahasa indonesia oleh (Rohana, 2017) dan skala kedua adalah skala prokrastinasi akademik yang dikembangkan penulis berdasar pada ciri prokrastinasi akademik menurut (Ferrari et al., 1995). Kedua instrumen tersebut telah teruji validitas dan reliabilitasnya. Pengukuran prestasi belajar menggunakan nilai Ujian tengah Semester pada semester ganjil 2021/2022. Hasil penelitian menunjukkan bahwa stres akademik dan prokrastinasi akademik memiliki hubungan negatif dengan prestasi belajar dan secara bersama-sama stres akademik dan prokrastinasi akademik mempengaruhi prestasi belajar. Harapan peneliti hasil penelitian ini dapat menjadi informasi dan pertimbangan untuk konselor sekolah atau guru BK dalam membeikan layanan kepada siswa. Selain itu, peneliti berharap untuk peneliti selanjutnya bisa melanjutkan penelitian pengembangan yang menghasilkan sebuah produk yang dapat membantu siswa terkait permasalahan stres akademik, prokrastinasi akademik dan prestasi belajar.